The world made new : why the Age of Exploration happened & how it changed the world - Aronson, Marc.; Glenn, John W. (Washington, D.C. : National Geographic, 2007)
Describes how the discoveries made by the Europeans around the time of Columbus changed the world. National Geographic has always given readers the bigger picture of our world. Now The World Made New shows children the bigger context of American history. Written by award-winning children's author Marc Aronson and John W. Glenn, this innovative title will lead children through the causes and consequences of the defining age of exploration. Its unique approach will provide children with new ways of thinking about and learning from history, and instill a lasting sense of our country's past. The World Made New provides a detailed account of the charting of the New World and the long-term effects of America's march into history. The text uses primary sources to bring history to life and features evocative profiles of the major explorers of the age. The book is beautifully illustrated with full-color artwork, multiple-time lines, and six custom National Geographic maps. The text and layout combine to provide an enlightening overview of New World exploration, and outline the historical context for the discoveries that literally changed the world. The narrative carries young readers through this age of glorious, and sometimes inglorious, adventure. Follow the timeline of history unfolding; how the early colonies were established; how dissemination of products like the potato, tomato, tobacco, and corn made the Americas a major part of the new world economy; and how the Caribbean became a major trading hub.
Introduction -- Causes: Why was there an age of exploration? -- Europe sets sail: Religion -- Competition -- Wealth -- Glory -- Knowledge -- Empires of the Americas: Inca -- Aztec -- Lost city -- Trade -- What happened: Explorers -- Columbus and the new world -- Age of exploration -- Cortés -- Pizarro -- Cartier -- De Soto -- Drake -- Consequences: How the explorers changed the world -- World joined: Disease -- Plants & animals -- Population -- Dinner -- Global gold -- Migration -- Ideas -- Ways of living -- Conclusion -- Place-finder map -- Biographical dictionary -- Glossary -- Sources & web sites -- Index.
Includes bibliographical references (p. 60-61) and index.
Keywords: Discoveries in geography -- Juvenile literature; Discoveries in geography; Juvenile works